Probation supervision as a network of relationships: Aiming to be thick, not thin. (September 2019) - Dominey, Jane
This article is about the networks of relationships (between people and between organisations) that underpin probation supervision. Drawing on evidence from a study researching these interactions, it develops two models of supervision ('thin' and 'thick') by taking themes that shape supervision and charting the interplay between them. The article develops these models in the increasingly fragmented landscape that has followed the Transforming Rehabilitation (TR) reforms in England and Wales. The concepts of 'thin' and 'thick' are used here to describe the supervisory network. Thin supervision describes a minimal and administrative approach to supervision. By contrast, thick supervision requires a network with strong and purposeful links. The article acknowledges the impact of public sector spending cuts on probation services and concludes by reflecting on the challenge of building and sustaining thick supervision in the current context.